Caritas in veritate: a different globatization and a new ethical conscience - Bazán Gayoso, Elizabeth (2010)
The world is currently undergoing an accelerated economic, technical, scientific, cultural globalization process that requires the understanding there of in its complexity and the modification of macro trends marked by injustice. To achieve genuine human development is urgent to have a people and community-oriented cultural approach open to transcendence, which entails a new ethical awareness.